2016
DOI: 10.1093/rheumatology/kew241
|View full text |Cite
|
Sign up to set email alerts
|

Most patients who reach disease remission following anti-TNF therapy continue to report fatigue: results from the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis

Abstract: Despite achieving clinical remission, many RA patients do not achieve complete remission of their fatigue. Therefore, despite being important in overall disease control, reductions in disease activity are not always sufficient to ameliorate fatigue, so other symptom-specific management approaches must be considered for those for whom fatigue does not resolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 17 publications
2
67
0
1
Order By: Relevance
“…On all three fatigue instruments utilized, patients showed significantly higher fatigue scores than age-and sex-matched healthy subjects. In the patients and healthy subjects, respectively, median fVAS scores were 51 (21-67) and 11 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20); FSS scores were 4 (2Á5-5Á3) and 1Á6 (1Á1-2Á2); and SF-36 Vitality subscale scores were 43 (25-55) and 73 (65-85) (Fig. 2).…”
Section: Fatigue Severity and Prevalencementioning
confidence: 97%
See 2 more Smart Citations
“…On all three fatigue instruments utilized, patients showed significantly higher fatigue scores than age-and sex-matched healthy subjects. In the patients and healthy subjects, respectively, median fVAS scores were 51 (21-67) and 11 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20); FSS scores were 4 (2Á5-5Á3) and 1Á6 (1Á1-2Á2); and SF-36 Vitality subscale scores were 43 (25-55) and 73 (65-85) (Fig. 2).…”
Section: Fatigue Severity and Prevalencementioning
confidence: 97%
“…Moreover, the impact of disease activity on fatigue in inflammatory diseases remains a controversial issue. Some investigators claim that fatigue increases with high disease activity, while others have not confirmed such a relationship . This issue has not yet been thoroughly studied in patients with psoriasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…inflammatory) remission. 17 Therefore, it is unlikely that inflammation alone is the single driver for RA fatigue.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…However, effective treatments for fatigue are limited. RA medications seem to have minimal effects on reducing fatigue (3)(4)(5). Programs such as cognitive behavioral therapy appear to have a positive impact (6), but the likelihood of such programs becoming widely available is unknown because of resource requirements.…”
Section: Introductionmentioning
confidence: 99%